2022
DOI: 10.1186/s13044-022-00133-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-Müllerian hormone in pre-menopausal women stratified according to thyroid function, autoimmunity and age

Abstract: Background AMH is a reliable index of ovarian reserve. It is not clear whether, or how much, thyroid function and/or thyroid autoimmunity can impair ovarian function and AMH secretion in the long term. Aim This retrospective cross-sectional study compared AMH levels in pre-menopausal women with/without positive thyroid autoimmunity or hypofunction. Methods From January 2019 to May 2022, AMH was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…A more recent study ( 105 ) in infertile women, including patients with subclinical and clinical hypothyroidism, confirmed a relationship between TSH levels and the ovarian reserve in women aged >35 years only. Although these data are not in agreement with other studies ( 93 , 101 104 , 106 ), one unit increase in TSH level was associated with a 25% increased risk of an AMH level <1.1 ng/ml and an increase in serum TSH values greater than the cutoff of 1.465 mIU/L was associated with a decrease in ovarian function in these patients ( 105 ). More recently ( 106 ) a Chinese study demonstrated that the ovarian reserve may be affected only in women with TSH levels >2.5 mIU/L and an anti-TPO Ab >100 IU/ml.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…A more recent study ( 105 ) in infertile women, including patients with subclinical and clinical hypothyroidism, confirmed a relationship between TSH levels and the ovarian reserve in women aged >35 years only. Although these data are not in agreement with other studies ( 93 , 101 104 , 106 ), one unit increase in TSH level was associated with a 25% increased risk of an AMH level <1.1 ng/ml and an increase in serum TSH values greater than the cutoff of 1.465 mIU/L was associated with a decrease in ovarian function in these patients ( 105 ). More recently ( 106 ) a Chinese study demonstrated that the ovarian reserve may be affected only in women with TSH levels >2.5 mIU/L and an anti-TPO Ab >100 IU/ml.…”
Section: Resultscontrasting
confidence: 84%
“…No effect of anti-TG Ab was detected on ovarian function (menstrual pattern) or biochemical/clinical hyperandrogenism ( 92 ). More recently, serum AMH levels were significantly higher in anti-TPO Ab-negative versus anti-TPO Ab-positive women, but it is important to note that patient age was significantly lower in anti-TPO Ab- negative versus anti-TPO- Ab-positive women, highlighting the influence of age on AMH levels ( 93 ). Conversely, other studies ( 58 , 94 , 95 ) reported high autoantibody levels against ovarian tissue in women with PCOS.…”
Section: Resultsmentioning
confidence: 99%